Eco-Fiqh: Pendekatan Maslahat Terhadap Amdal dan Konservasi Lingkungan - Muhammad yusuf (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
This study based on postulate that both maslahat and primary texts of Islam are never contaradicting essentially, where holy text is guidance for humankind for goodness of world and hereafter. Based on ‘maslahat approach’, appear idea of eco-fiqh to respond several envoronmental problems. This article aims to study about eco-fiqh which is based on maslahat approach (benefit) and analysis about environmental impact (amdal). To realize benefit of development, regulation of analysis about environmental impact must be obeyed, because it is supported by Islamic principle that “preventing the adverse effects is more prioritized than taking advantages”. Eco-fiqh guides a principle that prevention of environmental adverse effects for longer time than to take economic benefit for shorter time. Preserving the environment is prophetic doctrine and also a mainstream of Islamic doctrine which sometimes ignored. Preserving the environment is not only ‘tahsiniyat’ or ‘hajiyat’, or “dharuriyat’. Idea of eco-fiqh is an effort to put environmental conservation as mainstream of Islamic doctrine. Therefore, it brings about eco-piety beside spritual and social piety.